Mixing Performance Analysis and Optimal Design of a Novel Passive Baffle Micromixer - Yiwen Zheng; Yu Liu; Chaojun Tang; Bo Liu; Hongyuan Zou; Wei Li; Hongpeng Zhang (Micromachines, 2024)
Micromixers, as crucial components of microfluidic devices, find widespread applications in the field of biochemistry. Due to the laminar flow in microchannels, mixing is challenging, and it significantly impacts the efficiency of rapid reactions. In this study, numerical simulations of four baffle micromixer structures were carried out at different Reynolds numbers (Re = 0.1, Re = 1, Re = 10, and Re = 100) in order to investigate the flow characteristics and mixing mechanism under different structures and optimize the micromixer by varying the vertical displacement of the baffle, the rotation angle, the horizontal spacing, and the number of baffle, and by taking into account the mixing intensity and pressure drop. The results indicated that the optimal mixing efficiency was achieved when the baffle’s vertical displacement was 90 μm, the baffle angle was 60°, the horizontal spacing was 130 μm, and there were 20 sets of baffles. At Re = 0.1, the mixing efficiency reached 99.4%, and, as Re increased, the mixing efficiency showed a trend of, first, decreasing and then increasing. At Re = 100, the mixing efficiency was 97.2%. Through simulation analysis of the mixing process, the structure of the baffle-type micromixer was effectively improved, contributing to enhanced fluid mixing efficiency and reaction speed.